2001
DOI: 10.1088/0964-1726/10/4/325
|View full text |Cite
|
Sign up to set email alerts
|

Active-passive hybrid piezoelectric networks for vibration control: comparisons and improvement

Abstract: In this research, the passive damping and active control authority of several basic active-passive hybrid piezoelectric networks are analysed and compared. The comparison is performed in a nondimensionalized manner, throughout which the importance of the generalized electro-mechanical coupling coefficient is highlighted. It is concluded that these configurations yield very similar open-loop performance for the same electro-mechanical coupling. It is shown that larger electro-mechanical coupling leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
121
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(126 citation statements)
references
References 13 publications
3
121
0
2
Order By: Relevance
“…To solve (12), two more equations should be added to make the equations complete. The first is the correction equation in the correction step of the arc-length continuation procedure, and the other one can be obtained by imposing the phase of one harmonic of a DOF.…”
Section: International Journal Of Aerospace Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve (12), two more equations should be added to make the equations complete. The first is the correction equation in the correction step of the arc-length continuation procedure, and the other one can be obtained by imposing the phase of one harmonic of a DOF.…”
Section: International Journal Of Aerospace Engineeringmentioning
confidence: 99%
“…They showed that the RL piezoelectric shunt circuit performs like a dynamic vibration absorber; therefore, the resistor and inductor can be optimally tuned to structural resonance in a manner analogous to a mechanical vibration absorber. References [11,12] presented a vibration control method involving cyclic periodic structures using piezoelectric networks. It is shown that this approach can suppress all spatial harmonic components of the vibration, which cannot be achieved by the RL piezoelectric shunt circuit.…”
Section: Introductionmentioning
confidence: 99%
“…The system is then equal to an undamped absorber and the two characteristic poles around the absorption frequency can be noted. By varying the inductance value, two characteristic fixpoints whose amplitudes are independent from damping values can be equalized [8,11]. As the resistance increases, these Eigenmodes are getting damped, and the amplitudes of vibration decrease until an optimum is achieved.…”
Section: Rl-shuntmentioning
confidence: 99%
“…This leads directly to a relation between, e.g., the dimension and mass of the used transducers and the performance of an RL-shunted system. In order to artificially increase this coupling, [11] introduced an additional negative capacitance in series and parallel to the RL-shunt. Figure 5 shows the simplified scheme of an RLC-circuit, wherein the series negative capacitance can be realized with a circuit shown in Fig.…”
Section: Rlc-shuntmentioning
confidence: 99%
See 1 more Smart Citation